Code-switching practices and language preferences among multilingual learners in the English classroom - Karisma Putri; Poppy Rachman; Zainuddin Zainuddin (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This study examines the use of code-switching in English classroom instruction at Sekolah Indonesia Kuala Lumpur (SIKL), a transnational Indonesian school where English, Malay, and Indonesian are routinely used. Employing a qualitative descriptive research design, data were collected through four weeks of classroom observations, semi-structured interviews with three English teachers and selected students (Grades 10–12), and analysis of instructional documents and school language policies. The findings indicate that code-switching serves three main functions: pedagogical, social, and managerial. Pedagogically, it is used to clarify instructions, explain unfamiliar concepts, and support students’ comprehension. Socially, code-switching facilitates classroom interaction and encourages student participation. Managerially, it assists teachers in managing classroom routines and transitions. These findings suggest that code-switching functions as a strategic communicative resource in multilingual classrooms rather than as an indicator of linguistic deficiency. The study contributes to discussions on multilingual pedagogy by highlighting how code-switching supports instructional effectiveness in overseas Indonesian school contexts.